Analysis of satisfaction with lip appearance of students at a brazilian university institution – a pilot study - Galdino, Andresa Rayane Sarinho (2024)
Introduction: the lips are essential for the symmetry and aesthetics of the face, in addition to being often associated with characteristics of beauty and attractiveness. Objective: to analyze satisfaction with lip appearance of students at a brazilian university institution. Material and methods: it was carried out a cross-sectional, descriptive pilot study with a frequency analysis method. The sample consisted of thirty-three female dentistry students aged 18 to 30 years. A questionnaire was applied, formulated by the researchers, which included questions about the level of satisfaction/dissatisfaction and motivation/demotivation with different morphological aspects linked to lip appearance, the possibility and interest in performing aesthetic procedures on the lips, as well as questions to investigate influencing factors arising from the external environment, not linked to the individual aesthetic impression, which nourish the desire to perform lip interventions. Results: it was found that 78.8% of participants reported satisfaction with their lip appearance and that 63.7% of them would find it easy to perform aesthetic procedures on their lips. In most of the questions answered, the rate of dissatisfaction was lower than the rate of motivation to perform aesthetic procedures related to different lip morphological aspects. Conclusion: the majority of students reported being satisfied with their lip appearance. However, the motivation to perform lip aesthetic procedures remained constant, with increasing lip volume being the intervention most desired by the sample. Additionally, monitoring lip procedures carried out by well-known or famous people was a factor that generated interest in the participants of this research to also carry out possible aesthetic interventions on the lips.